John W. A. Sanford correspondence - Sanford, John W. A., 1798-1870.
ALS written by Sanford to William Schley at the close of the Creek War, mentioning the service of Gen. Winfield Scott.
U.S. representative and public official from Georgia, farmer, and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Scott, Winfield, -- 1786-1866.; Schley, William, -- 1786-1858 -- Correspondence; Creek War, 1836.; Army officers; Farmers; Public officials -- Georgia; Representatives, U.S. Congress -- Georgia